2016
DOI: 10.1038/ncomms11868
|View full text |Cite
|
Sign up to set email alerts
|

DELLA-mediated PIF degradation contributes to coordination of light and gibberellin signalling in Arabidopsis

Abstract: Light and gibberellins (GAs) antagonistically regulate hypocotyl elongation in plants. It has been demonstrated that DELLAs, which are negative regulators of GA signalling, inhibit phytochrome-interacting factors 3 and 4 (PIF3 and PIF4) by sequestering their DNA-recognition domains. However, it is unclear whether there are other mechanisms of regulatory crosstalk between DELLAs and PIFs. Here, we demonstrate that DELLAs negatively regulate the abundance of four PIF proteins through the ubiquitin–proteasome sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
174
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(192 citation statements)
references
References 59 publications
(110 reference statements)
7
174
0
Order By: Relevance
“…Several independent studies demonstrated that the DELLA proteins physically interact with PIFs and sequester them into an inactive complex to restrain PIFs from binding to their targets (de Lucas et al, 2008; Feng et al, 2008; Gallego-Bartolomé et al, 2010). Recently it has been also shown that DELLAs not only sequester PIFs but also induce their degradation (Figure 3A), and more importantly, DELLAs-mediated degradation of PIFs functions independently of well-established phyB/LRBs pathways (Li et al, 2016). Thus, crosstalks between light and GA signaling pathways play an important role in fine-tuning germination and photomorphogenesis for optimal growth and development of plants.…”
Section: Pifs Integrate Light and Hormone Signaling Pathwaysmentioning
confidence: 95%
“…Several independent studies demonstrated that the DELLA proteins physically interact with PIFs and sequester them into an inactive complex to restrain PIFs from binding to their targets (de Lucas et al, 2008; Feng et al, 2008; Gallego-Bartolomé et al, 2010). Recently it has been also shown that DELLAs not only sequester PIFs but also induce their degradation (Figure 3A), and more importantly, DELLAs-mediated degradation of PIFs functions independently of well-established phyB/LRBs pathways (Li et al, 2016). Thus, crosstalks between light and GA signaling pathways play an important role in fine-tuning germination and photomorphogenesis for optimal growth and development of plants.…”
Section: Pifs Integrate Light and Hormone Signaling Pathwaysmentioning
confidence: 95%
“…Strikingly, a recent study showed that DELLA proteins not only sequester PIFs but also induce their degradation to regulate target gene expression (Li et al, 2016). Thus, DELLA proteins and phytochromes regulate PIFs in a similar fashion.…”
Section: Factors Inhibiting the Dna-binding Ability Of Pifsmentioning
confidence: 99%
“…In a recent study, DELLA proteins also were shown to promote the degradation of all four PIFs through the 26S proteasome pathway under both dark and light conditions (Li et al, 2016). Thus, DELLAs inhibit PIF activity not only by sequestration but also by PIF degradation to regulate hypocotyl elongation.…”
Section: Factors Controlling Pif Abundance Under Darknessmentioning
confidence: 99%
“…Recently, PIF3 was shown to be phosphorylated directly by photoregulatory protein kinases (PPKs), and targeted by LRB Cullin 3 E3 ligases together with phyB for ubiquitination and degradation (21,22). DELLAs promote the degradation of PIF3 and PIF4 in a light-independent manner by recruiting an unknown E3 ligase (23). BIN2, a protein kinase involved in BR signaling, has also been shown to mediate phosphorylation and degradation of PIF3 via the 26S proteasome pathway (24).…”
mentioning
confidence: 99%